Activation of Pd-precatalysts by organic compounds for vinyl-addition polymerization of a norbornene derivative. Issue 35 (31st March 2021) - Karpov, Gleb O.; Ren, Xiang-Kui; Melnikova, Elizaveta K.; Bermeshev, Maxim V.
Abstract : An approach to activating Pd-complexes without using additives such as Lewis acids has been developed for addition polymerization of norbornenes. Abstract : An approach to activating Pd-complexes without using additives such as Lewis acids has been developed for addition polymerization of norbornenes. Aryl iodides and aryl diazonium salts were efficiently applied as cocatalysts to Pd(0)- and Pd(2+)-complexes. The developed systems catalyzed polymerization of norbornenes containing bulky and polar functional groups both in an inert atmosphere and air resulting in soluble and high-molecular-weight saturated polymers.